Anesthesia unplugged - Gallagher, Christopher J.; Ginsberg, Steven H.; Lewis, Michael C. (McGraw-Hill Medical, 2012)
"An amusing step-by-step approach to learning basic anesthesia techniques and procedures. Written in a humorous, entertaining style, Anesthesia Unplugged, 2e helps anesthesiologists in training develop the procedural skills necessary for the optimal care of the anesthetized patient. Featuring an easy-to-navigate atlas-style presentation, the book covers all relevant anesthesia procedures, detailing indications, contraindications, equipment, and technique. Key Selling Features: The humerous, engaging tone helps readers remember the procedures. Large, atlas-style photos illustrate equipment, procedure, and technique. Covers the entire spectrum of perioperative, ambulatory, regional, and general procedures" -- Provided by publisher.